Efficacy of Neuraminidase Inhibitors against H5N6 Highly Pathogenic Avian Influenza Virus in a Nonhuman Primate Model - Nguyen, Cong Thanh; Suzuki, Saori; Itoh, Yasushi; Ishigaki, Hirohito; Nakayama, Misako; Hayashi, Kaori; Matsuno, Keita; Okamatsu, Masatoshi; Sakoda, Yoshihiro; Kida, Hiroshi; Ogasawara, Kazumasa (Antimicrobial agents and chemotherapy, 2020)
Attention has been paid to H5N6 highly pathogenic avian influenza virus (HPAIV) because of its heavy burden on the poultry industry and human mortality. Since an influenza A virus carrying N6 neuraminidase (NA) has never spread in humans, the potential for H5N6 HPAIV to cause disease in humans and the efficacy of antiviral drugs against the virus need to be urgently assessed. We used nonhuman primates to elucidate the pathogenesis of H5N6 HPAIV as well as to determine the efficacy of antiviral drugs against the virus. Attention has been paid to H5N6 highly pathogenic avian influenza virus (HPAIV) because of its heavy burden on the poultry industry and human mortality. Since an influenza A virus carrying N6 neuraminidase (NA) has never spread in humans, the potential for H5N6 HPAIV to cause disease in humans and the efficacy of antiviral drugs against the virus need to be urgently assessed. We used nonhuman primates to elucidate the pathogenesis of H5N6 HPAIV as well as to determine the efficacy of antiviral drugs against the virus. H5N6 HPAIV infection led to high fever in cynomolgus macaques. The lung injury caused by the virus was severe, with diffuse alveolar damage and neutrophil infiltration. In addition, an increase in interferon alpha (IFN-α) showed an inverse correlation with virus titers during the infection process. Oseltamivir was effective for reducing H5N6 HPAIV propagation, and continuous treatment with peramivir reduced virus propagation and the severity of symptoms in the early stage. This study also showed pathologically severe lung injury states in cynomolgus macaques infected with H5N6 HPAIV, even in those that received early antiviral drug treatments, indicating the need for close monitoring and further studies on virus pathogenicity and new antiviral therapies.